The art of makeup as an aesthetic value in the cinematic film - Qureshi Saadi Ahmed saeid (Journal of Architecture, Art & Humanistic Science, 2023)
It is known that visual art is the art that is capable of making the spectator turns from state to another. Cinema is considered one of the most powerful and effective visual arts, and it has the ability to influence and persuade.In the beginning, in the field of visual effects cinema depended on traditional and simple methods that commensurate with the culture of the spectator at this time, then the technical progress was clearly and rapidly followed in the technological fields that helped to apply all kinds of optical illusions, which greatly contributed to change the shape and content of the movie."The art of Makeup” is considered one of the most important branches of optical illusions.Where it comes to mind that the art of makeup is only related to beautifying artists and hiding facial flaws to show them brilliantly, but the truth is that the art of makeup is the art of changing the appearance of the real face of the actor in a way that suits the character he performs, by using powders, colors….etc., to create certain facial features required to express the character or to be reincarnated.In addition to its application by many people to attend various artistic and masquerade events, and we often notice many people are using it in daily life, and they are often teenagers.Also cinematic makeup can deliver any kind of information to viewers without using words or wasting time, make-up in dramas differs from ordinary make-up, as it is subject to study as a self-stand art, because make-up has to be compatible with bright lighting, decorative angles and accessories.This type of art has become a pillar that specialized institutes are opened based on it, where young talents who found inspiration in cinematic works and other arts to paint them on faces and bodies using various colors and accessories could be contained, so that this type of art opens doors in front of their imagination to be creative and show their ideas no matter how strange and crazy it seems.